Psychosocial outcomes and quality of life among school‐age survivors of retinoblastoma - Morse, Melanie; Parris, Kendra; Qaddoumi, Ibrahim; Phipps, Sean; Brennan, Rachel C.; Wilson, Matthew W.; Rodriguez‐Galindo, Carlos; Goode, Kristin; Willard, Victoria W. (Pediatric blood & cancer, 2023)
Background Retinoblastoma is the most common intraocular childhood cancer and is typically diagnosed in young children. With increasing number of survivors and improved medical outcomes, long‐term psychosocial impacts need to be explored. Thus, the current study sought to assess functioning in school‐aged survivors of retinoblastoma. Procedure Sixty‐nine survivors of retinoblastoma underwent a one‐time evaluation of psychosocial functioning. Survivors (Mage = 10.89 years, SD = 1.07 years; 49.3% male; 56.5% unilateral disease) and parents completed measures of quality of life (QoL; PedsQL) and emotional, behavioral, and social functioning (PROMIS [patient‐reported outcome measurement information system] Pediatric Profile, BASC‐2 parent report). Demographic and medical variables were also obtained. Results On the whole, both survivors and caregivers indicated QoL and behavioral and emotional health within the typical range of functioning. Survivors reported better physical QoL compared to both parent report and a national healthy comparison sample, whereas caregivers reported that survivors experienced lower social, school, and physical QoL than a healthy comparison. Regarding behavioral and emotional health, survivors indicated more anxiety than a nationally representative sample. Parents of female survivors endorsed lower adaptive scores than parents of male survivors. Conclusions Results indicated that survivors of retinoblastoma reported QoL and behavioral and emotional health within normal limits, although parents appear to perceive greater impairment across several assessed domains. Understanding both survivor and parent reports remains important for this population. Future research should explore psychosocial functioning of these survivors as they transition to adolescence and early adulthood, given the increased independence and behavioral and emotional concerns during these developmental periods.